PESANTREN SALAFIYAH DI ERA GLOBALISASI - Hasbi Indra (Universitas Islam Negeri Fatmawati Sukarno, 2016)
The research qualitative to the traditional islamic boarding school (pesantren salafiyah)are basesthe scholar prespektive through books, journals and so on with descriptive analisys by normative, filosofis and sociologis.The research are tries to description how pesantren salafiyah have 1.800.000 more students to readiness of them to face the fenomenan globalization era. Pesantren salafiyah areborn in colonialismat Walisongoera as a institution learn Islamic knowledge. Those all institutionare established by community and now thats atthe remote area. The institutionsnow have 1.882.901 of 3.876.696 student and 18.232 of 29.535 institutions from three types of be traditional pesantren, combinate pesantren and modem pesantren. Thatinstitution just learn Islamic knowledge through Islamic classical texbook (kitab kuning) most of institution are not learn science such as MIFA. The traditional pesantren now are faced of globalization fenomenon.Globalization in this era are the human relation with unlimited time in the world. Through the development of toolscommunications or throughfaxcimile, human as faras have an information in the other continents. We wach TV a wars saw sad the happens, like wars soldier American and Irak, islamic state Irak and Syria (ISIS) breakthroughislamic inherited the golden era.The fenomenon of the develompement of technology in globalization era are challengs of pesantren Salafiyah. Its istitutions must product alumnus are ready competete with knowledge, scineces and even skill and santri are introduce with tools of technology learning. So, all santri’s must all ready compatete the globalization era, and the institution must manage with professional